Mechanical behavior of high-performance steel ring restrainers with negative Poisson's ratio effect. (September 2022) - Wang, Zhanfei; Wu, Huan; Sui, Weining; Ren, Hao; Sun, Jubo
Abstract: The steel ring restrainer (SRR) is a novel restrainer for bridges, which can prevent the unseating of bridges when an earthquake occurs. The traditional SRR is commonly made of mild steel, so it has the limitation of low strength and insufficient safety margin. In this paper, a new type of high-performance steel with negative Poisson's ratio effect (NPR steel) is introduced for use in an SRR. Finite element (FE) models of SRRs are constructed, and the credibility of the FE model is validated based on previous experiments. Then, the FE models of SRRs under the mild steel, high-strength steel, and NPR steel are established, and the mechanical performance of SRRs fabricated of different steel grades is compared. The comparison results show that the macroscopic deformation processes of SRRs made of different steel grades during operation are similar, but their mechanical properties differ. Among them, the SRR made of NPR steel (SRR-NPR) has the advantage of high strength, excellent ductility and sufficient safety margin, so it can overcome the limitations of traditional SRRs. Subsequently, in order to further explore the mechanical behavior of SRR-NPR, several FE models of SRR-NPR are supplemented by changing the design parameters. The analytical results indicate that the trends in the influence of the design parameters on the mechanical properties of SRR-NPR are similar to those of traditional SRRs. However, the sensitivity of the mechanical properties of SRR-NPR to design parameters is higher than that of traditional SRRs. Finally, based on the results of numerical analyses, the problem that the conventional method of predicting the relationship between force and displacement of SRRs is inapplicable to SRR-NPR is overcome, and prediction formulas of SRRs that considers more factors are proposed and verified.